One of the goals of Gumilev Eurasian National University is to produce high-quality textbooks in the native language - Abdirayim Бақытжан (Рroblems of engineering and professional education, 2023)
One of the goals of Gumilev Eurasian National University is to produce high-quality textbooks in the native language